2016
DOI: 10.1038/sc.2015.235
|View full text |Cite
|
Sign up to set email alerts
|

SCIPA Com: outcomes from the spinal cord injury and physical activity in the community intervention

Abstract: Study design: Quasi-experimental translational study with pre-and post-measures. Objectives: To determine the effects of the Spinal Cord Injury and Physical Activity in the Community (SCIPA Com) intervention on leisure-time physical activity (LTPA) and associated outcomes among participants with spinal cord injury (SCI). Setting: Young Men's Christian Associations and community fitness centers, Australia and New Zealand. Methods: SCIPA Com consisted of three stages: (i) training exercise professionals via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Improvements in selfesteem, QoL, and fitness levels have been reported following community exercise programs in individuals with SCI. 16,17,27,28,[30][31][32] This study revealed a statistically significant increase in QoL, as demonstrated by the LiSAT-9 outcome measure. Garshick et al found a similar positive association between prescribed exercise programs and a higher satisfaction of life for individuals with SCI.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Improvements in selfesteem, QoL, and fitness levels have been reported following community exercise programs in individuals with SCI. 16,17,27,28,[30][31][32] This study revealed a statistically significant increase in QoL, as demonstrated by the LiSAT-9 outcome measure. Garshick et al found a similar positive association between prescribed exercise programs and a higher satisfaction of life for individuals with SCI.…”
Section: Discussionsupporting
confidence: 63%
“…37 Compared to the able bodied community, individuals with SCI tend to have a lower QoL and lack accessible and targeted community programs. [15][16][17] Additionally, individuals with SCI have increasing life expectancy, as well as, increasing risk of secondary health conditions. 1,10 Community-based programs, such as Spinal Mobility, address the aforementioned barriers to exercise at no cost to participants and may be the framework for providing exercise opportunities for the aging population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Many barriers exist to participation in leisure time physical activity by people with SCI, including motivation, finances, and accessibility to specialized programs or equipment. 32 Programs to overcome some of these barriers are now being developed 28 and are similar to the exercise program delivered to UBE in this study.…”
Section: Discussionmentioning
confidence: 99%